The Use of Standard and Non-Standard Indonesian by Universitas Negeri Medan Students’ in Digital Communication in the Social Media Era - Imel Tri Ulina Hutabarat; Deswita Syahputri; Risky Ansipar Hutapea; Muhammad Surip (Faculty of Tarbiyah nad Teacher Training, 2026)
The growth of social media has significantly impacted language use among university students when communicating digitally. This study aims to (1) describe how students at Universitas Negeri Medan utilize standard and non-standard Indonesian in their daily digital interactions, (2) identify deviations from standard Indonesian language rules, and (3) explore students' perspectives regarding the impact of social media on their mastery of standard language. A descriptive qualitative approach was employed in this study. Data were collected through open-ended questionnaires from five active students across various majors and analyzed thematically. The results indicate that students consciously choose standard Indonesian for formal and academic contexts (e.g., communicating with lecturers, completing assignments), whereas non-standard language or slang is more frequently used in informal interactions on WhatsApp, Instagram, and TikTok. Common deviations include non-standard abbreviations, slang, English code-mixing, and typographical errors, which are mostly driven by habit, social environment, and the need for rapid communication. Despite these deviations, students recognize the importance of using standard Indonesian to maintain professionalism, politeness, and national identity. They also implement strategies such as reading academic texts and practicing formal language to maintain their standard language skills. This study contributes to the sociolinguistic discussion regarding language change in the digital era.